Respostas
respondido por:
9
somando as duas equações:
x + 2x + y - y = 5 + 10
3x = 15
x = 5
5 + y = 5
y = 0
respondido por:
5
1) x + y = 5
2) 2x - y = 10
1) x + y = 5
y = 5 - x
2) 2x - y = 10
2x - (5-x) = 10
2x - 5 + x = 10
3x - 5 = 10
3x = 5 + 10
3x = 15
x = 15/3
x = 5
1) x + y = 5
5 + y = 5
y = 5 - 5
y = 0
Par ordenado solução: (5, 0)
2) 2x - y = 10
1) x + y = 5
y = 5 - x
2) 2x - y = 10
2x - (5-x) = 10
2x - 5 + x = 10
3x - 5 = 10
3x = 5 + 10
3x = 15
x = 15/3
x = 5
1) x + y = 5
5 + y = 5
y = 5 - 5
y = 0
Par ordenado solução: (5, 0)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás